2015
DOI: 10.1007/s40610-015-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Biology of Tendon: Mechanisms for Renewal and Repair

Abstract: Understanding the molecular and cellular mechanisms underlying tissue turnover and repair are essential towards addressing pathologies in aging, injury and disease. Each tissue has distinct means of maintaining homeostasis and healing after injury. For some, resident stem cell populations mediate both of these processes. These stem cells, by definition, are self renewing and give rise to all the differentiated cells of that tissue. However, not all organs fit with this traditional stem cell model of regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 134 publications
(118 reference statements)
0
39
0
1
Order By: Relevance
“…In regard to expression and synthesis of proteins from tendon cells, it has been shown that older rats demonstrated a reduced mRNA expression of collagen (I, III and V) whereas the protein content of collagen types estimated by immunohistochemistry was unchanged with ageing (Goh et al . ; Dyment & Galloway, ; Zhang et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to expression and synthesis of proteins from tendon cells, it has been shown that older rats demonstrated a reduced mRNA expression of collagen (I, III and V) whereas the protein content of collagen types estimated by immunohistochemistry was unchanged with ageing (Goh et al . ; Dyment & Galloway, ; Zhang et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical repair represents one treatment option to improve function and decrease pain. Despite extensive research aimed at improving surgical outcomes, repair failure remains a common problem . High failure rates may be due to a tendon environment that does not support a prompt, effective healing response .…”
Section: Introductionmentioning
confidence: 99%
“…There is still debate regarding whether tendon healing is an intrinsic or extrinsic process [9,10]. The supraspinatus tendon has a number of surrounding tissues that could harbor cells that contribute to the healing response.…”
Section: Introductionmentioning
confidence: 99%